Exclusive dielectron production in ultraperipheral Pb+Pb collisions at sNN $$ \sqrt{s_{NN}} $$ = 5.02 TeV with ATLAS. (Tufts University. Tisch Library., 2023)
Keywords : Heavy Ion Experiments, Heavy-Ion Collision.; Springer Open.